Combined Application of Er:YAG and Nd:YAG Lasers Enhances Osseointegration at Dental Bone-Implant Interface - Zhao, Tianyuan; Li, Meihua (Frontiers in Materials, 2022)
The combination of bone and implant surface is a dynamic biological process. By improving the osseointegration efficiency of the bone tissue around the implant surface, the implant can obtain long-term stability.In this study, we have investigated the potential applications of dual-wavelength lasers (Er: YAG laser and Nd: YAG laser) in implantations and observed their possible efficacy in promoting tissue repair around the implant. The animal experimental model of rabbit femoral defect implant was employed to simulate the process of tissue reconstruction around the implant in human. The results indicated that by Micro CT observation, it was obvious that the bone mineral density (BMD) values of the dual-wavelength laser group were significantly higher than other groups. Furthermore, VG staining clearly showed that there was no obvious physiological gap detected between the implant and the surrounding bone tissues in the dual-wavelength laser group. HE staining further revealed that no significant influx of inflammatory cells were observed around the implants. Immunohistochemical staining of OCN and VEGF showed that the positive area percentages of the dual-wavelength laser group were significantly higher than other groups at the same time point. Therefore, the application of dual-wavelength laser in implantations can exhibit a positive effect on promoting the reconstruction of bone tissues.